Use of e-resources to satisfy academic information needs by the undergraduates: a case study of Faculty of Science, University of Colombo - Wijetunge, Pradeepa (My University, 2011)
A pilot survey concerning the Use of e-resources to satisfy the academic and personal information needs by the final year undergraduates of the Faculty of Science, University of Colombo was conducted in December 2010. Out of total of 150 students 50 (33%) were selected for the survey and there were 40 responses. Removing 5 incomplete responses, 35 (87.5%) were analysed. Students responded to 24 questions which elicited information on their information behavior but this paper discusses only the aspects related to their use of information for academic purposes. Analysis discusses the types of academic assignments they receive, frequency of consulting various information sources, evaluation of library and web material, people they consult for assistance, preferred research styles, use of e-productivity tools, factors considered as important in course-related research and attitudes towards difficulty of various stages of the research process. Based on the findings several interpretations and recommendations are made. Nevertheless this survey does not represent a comprehensive picture of the use of e-resources by the undergraduates of the Sri Lankan universities. The survey concentrates on science students who are conversant with the use of IT and English language. Survey of other disciplines and other academic years would yield different results